Antenatal Corticosteroids for Maturity of Term or Near Term Fetuses: Systematic Review and Meta-Analysis of Randomized Controlled Trials. Issue 3 (September 2017) - Saccone, Gabriele; Berghella, Vincenzo
Abstract : ( BMJ. 2016;355:i5044) One of the significant causes of early neonatal morbidity and mortality in the United States is respiratory distress syndrome (RDS). The use of prophylactic corticosteroids in preterm pregnancies is known to hasten lung maturation and decrease the occurrence of RDS.